The Influence of Harvesting Period on Lipid Associated Antioxidant Activity of Semicontinuously Grown Chlorella vulgaris - Tjandara Chrismadha; Diani Sartika; Iriani Setyaningsih; Uju Uju (ANNALES BOGORIENSES, 2010)
A green alga,  Chlorella vulgaris  was grown semi-continuosly at various harvesting periods, and the lipid content and its associated antioxidant activity was examined. The harvesting periods were 9, 18, and 27 days, while the algal culture was placed  in 10 L glass  bottles provided with aeration  for gas exchange and  mixing. Light  was  obtained  from  440  watt  cool  fluorescent  lamps  placed  at  one  side  of  the  culture.  Room temperature was  26-32C.  Algal  lipid  extraction  was  done  based  on  liquid  phase  separation  of  methanol :chloroform:water  and  the  antioxidant  activity  was  examined  by  means  of  oxidation  inhibitory  in ethanol emulsified  limnoleic  acid.  In  addition,  a  TLC  analysis  was  performed  to  identify  the  antioxidant compouns soluble  in  the  lipid.  The  results  showed  that  harvesting  per iod  had  a  significant  influence  on  the algal lipid  content,  which  were  11.94,  12.96,  and  16.51%  of  the  dry  weight  in  the  culture  with  harvesting periods of 9, 18, and 27 days, respectively. No remarkable effect of the  harvesting period on the  antioxidant activity, which were observed to inhibit oxidation of linoleic acid up to 67-71%. There were five compounds found can  be associated   with  the  algal  antioxidant  activity,  which  were  pheophorbide -a,  chlorophyll-b,chlorophyll-a, phaeophytin-a, -carotene, and an unidentified one. Key words: microalgae, Chlorella vulgaris, lipid, antioxidant, harvesting period